(3JMQjQ cJGH GdGcQ dKGhPhSjhSs - (3CMeO Hf eMeO GdZRGdjs
(3ChdgG (B:s
(3HYO GdHSedI hGdOjHGLI hbO GeQ HfbdI ef GdjhfGfjI Edi GdYQHjI CHh GdYHGS CMeO Hf GdeYJUe HGddg aJhdj fbdI bSWG GHf dhbG Edj GdTcd GdNGeS ef GdebGdI GdKGdKI Ke ZjQg hGUdMI KGHJ Hf bQI s
(3BNQgG (B:s
(3gh JSYI hNeShf TcdkG haj HYV GdfSN KeGfjI hNeShf s
(3Vef eLehY , JQJjHgG (B: 5s
(3HgG fXGe GdJYbjHIs
(3hgh KdGK ebGdGJ hNeShf TcdkGs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3eJaQbGJs